Respuestas

2013-10-06T16:16:05+02:00

(-3) x (-2) + (-3) x 9 - (-3) x 3 - 3
Factor común (-3)
= (-3)[(-2) + 9 - 3 +1]
= (-3)(-2 + 9 -3 + 1)
= (-3)(5)
= - 10  RESULTADO FINAL

 (-5) x [ 8 + 4/5 + ( -2) 
Aplicando la propiedad distributiva
= (-5)x8 + (-5)(4/5) + (-5)(-2)
= - 40 - 4 + 10
= - 34   RESULTADO FINAL

MDC  ( 72 , x ) = 6  y  mcm (72, x ) = 3096 
Propiedad importante entre mcm y mdc:
           mcm(a,b) x mdc(a,b) = axb
Luego:
                6.3096 = 72.x
                        x = 6.3096/72
                           = 258
                                            x = 258  RESULTADO FINAL